2022
DOI: 10.3389/fpsyt.2022.840095
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Reactive Aggression in Adult Attention-Deficit/Hyperactivity Disorder

Abstract: Despite not being part of the core diagnostic criteria for attention-deficit/hyperactivity disorder (ADHD), emotion dysregulation is a highly prevalent and clinically important component of (adult) ADHD. Emotionally dysregulated behaviors such as reactive aggression have a significant impact on the functional outcome in ADHD. However, little is known about the mechanisms underlying reactive aggression in ADHD. In this study, we aimed to identify the neural correlates of reactive aggression as a measure of emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…We requested data from all ADHD case-control studies that included 16S fecal gut-microbiome samples, identified in two recent systematic reviews 13, 16 , see Supplementary Section 1.1, Table 1 and Supplementary Figure 15. We received clinical information and raw sequencing data from four adult cohorts (comprising the three articles including adults published to date: the NeuroIMAGE cohort 20, 21 and the Mental-Cat cohort from the Vall d’Hebron Research Institute in Barcelona (VHIR) 19 ; and unpublished data from the MIND-Set cohort 27 and our own cohort IMpACT2-NL 28 .…”
Section: Methodsmentioning
confidence: 99%
“…We requested data from all ADHD case-control studies that included 16S fecal gut-microbiome samples, identified in two recent systematic reviews 13, 16 , see Supplementary Section 1.1, Table 1 and Supplementary Figure 15. We received clinical information and raw sequencing data from four adult cohorts (comprising the three articles including adults published to date: the NeuroIMAGE cohort 20, 21 and the Mental-Cat cohort from the Vall d’Hebron Research Institute in Barcelona (VHIR) 19 ; and unpublished data from the MIND-Set cohort 27 and our own cohort IMpACT2-NL 28 .…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, these neuropsychological functions are closely related to salience-based information processing in the brain ( Seeley, 2019 ; Lugrin et al, 2023 ). Dysfunctional alterations in the salience network (SN) have been observed in various psychiatric disorders, including ADHD, OCD, post-traumatic stress disorder, and schizophrenia ( Berg et al, 2021 ; Huang et al, 2022 ; Jakobi et al, 2022 ; Tomiyama et al, 2022 ). In TD, the non-tic symptoms may rely on abnormalities of the cortical hubs within the SN, such as the anterior cingulate cortex (ACC), the ventral anterior insular cortex, and the temporoparietal junction (TPJ; Kucyi et al, 2012 ; Seeley, 2019 ; Uddin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%